(untitled) (Italian Journal of Public Health, 2012)
Background: data on the prevalence of use, beliefs and attitude towards doping substances and practices among Italian athletes are scarce. Methods: we interviewed 508 Italian athletes in sports facilities, using an anonymous structured questionnaire to collect information on the athletes’ beliefs about the role in performance and side effects of selected doping practices and substances, the reasons for use, obstacles in obtaining drugs, responsibility in the decision, changes in use in recent years, and anti-doping controls. Results: among the athletes, 88.2% believed that supplements were effective to improve performance and 4.8% that they were potentially dangerous. They believed that 87.0% of top-level athletes frequently use supplements, namely 69.1% anti-inflammatories and 56.9% creatine. Doping was widespread in the opinion of 87.4% of athletes, and 45.3% thought it was used at all competition levels. Among those interviewed, 43.9% reported that athletes and coaches together were responsible for use, and 25.2% that it was easy to obtain substances. Lastly, 34.8% believed that doping use increased during 2002-05, and 54.7% thought that anti-doping controls should be more frequent. Conclusions: this survey indicates that athletes believe that doping (mainly supplement use) is widespread at all competition levels, that athletes are aware of the seriousness of adverse effects and ask for more severe control and emphasis on potential dangers in the press.